Covid 19 Governance in Indonesia: A Systematic Literature Review - Nazaruddin Malik (Universitas Muhammadiyah Malang, 2022)
This study aims to categorize the dominant concepts or themes in the study of governance in handling the Covid-19 pandemic in Indonesia. The dominant concept is categorized based on cluster grouping. This study uses a systematic literature review method by collecting various previous studies to find strategies and problems in managing the COVID-19 pandemic in Indonesia. The main data source used is articles from the Scopus database. This research reveals that previous studies on the governance of handling Covid-19 in Indonesia are related to four dominant concepts, namely regional government, economy, impact, and spread. The dominant concept of regional government is related to the role of regional governments in making and implementing policies for handling Covid-19 at the regional level. The dominant concept of the economy is related to the focus of handling Covid-19 which is directed at maintaining economic stability and development carried out through various forms of policies and program activities, both at the national and regional levels. The concept of impact is an effort by the Indonesian government to minimize the negative impact of the Covid-19 crisis on the economy and development. The spread is the Indonesian government's efforts to minimize the spread of Covid-19. The four dominant concepts are interrelated with each other, which confirms that the governance of handling Covid-19 in Indonesia is governance that prioritizes the role of the government, focuses on stability, economic growth, and handling the impact and spread of Covid-19.